Exploring social isolation among Black parents who have children with autism: research proposal - Boateng, Josephine (My University, 2024)
According to Dis/ability critical race studies (DisCrit), inequalities based on disability do not exist separately from those in other domains of life, such as race. Instead, they intersect, building upon our identity in ways that amplify one's discrimination and the discrimination of those with disabled adjacent identities (e.g., parents) (Annamma et al., 2013; Pearson et al., 2023). This literature allowed me to marry my interests in race and health to explore the (social) implications that autism has in the parenting community. As such, through my partnership with Autism Edmonton, I explored how inequalities (i.e., ableism and racism) present within Canada exist in a multitude of ways that impact the lived experiences of those with disabled adjacent identities, specifically Black parents of children with autism. This presentation summarizes a research proposal that was developed for Autism Edmonton as a community partner for a fourth-year independent study course. Which explores the subjective experience of parenthood and how it becomes impacted by social factors such as race and disability. In order to study this topic, we propose future research that uses phenomenology and vignettes to center the voices of Black parents of children with autism (Creswell, 2014; Creswell, 2018; Starks & Trinidad, 2018). This will give researchers and community organizations such as Autism Edmonton a deep understanding of the experiences of Black parents of children with autism.
Presented on April 19, 2024 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: autism; parenthood; inequalities; racism